CHARACTERISTIC OF ROCK SLOPE DETERIORATION - THANKARAJ, THEEVASHINI (Universiti Teknologi PETRONAS, 2018)
This report fundamentally discusses the preliminary stage of the research dune so far on the topic Characteristics of Rock Slopes Deterioration. In rock slope projects, there are many cases of instability and failure. Therefore, the characteristic of rock should be fully considered in the stability analysis of rock slope. The objective of' this study is to gather deterioration processes of rock slopes, to access the effect of deterioration to rock instability and to obtain the factor of safety of the deteriorated rock. The factor of safety of the deteriorated rock is obtained through the GEO5 software and the Monte Carlo simulation was done using the ROCKTOPPLE v1.0 software. Both software’s were used to obtain the factor of safety with the same set of design parameters.